Femtosecond energy relaxation in suspended graphene : phonon-assisted spreading of quasiparticle distribution - Gurzadyan, Gagik G. (2013)
Ultra-fast optical measurements of few-layer suspended graphene films grown by chemical vapor deposition were performed with femtosecond pump–probe spectroscopy. The relaxation processes were monitored in transient differential transmission (ΔT/T) after excitation at two different wavelengths of 350 and 680 nm. Intraband electron–electron scattering, electron–phonon scattering, interband Auger recombination and impact ionization were considered to contribute to ΔT/T. All these processes may play important roles in spreading the quasiparticle distribution in time scales up to 100 fs. Optical phonon emission and absorption by highly excited non-equilibrium electrons were identified from ΔT/T peaks in the wide spectral range. When the probe energy region was far from the pump energy, the energy dependence of the quasiparticle decay rate was found to be linear. Longer lifetimes were observed when the quasiparticle population was localized due to optical phonon emission or absorption.